2014
DOI: 10.11118/actaun201159010067
|View full text |Cite
|
Sign up to set email alerts
|

An experimental comparison of methods for somatic cell count determination in milk of various species of mammals

Abstract: HANUŠ, O., SOJKOVÁ, K., HANUŠOVÁ, K., SAMKOVÁ, E., HRONEK, M., HYŠPLER, R., KOPECKÝ, J., JEDELSKÁ, R.: An experimental comparison of methods for somatic cell count determination in milk of various species of mammals. Acta univ. agric. et silvic. Mendel. Brun., 2011, LIX, No. 1, pp. 67-82 Somatic cell count (SCC) is important foodstuff , hygienic and health indicator of milk and animal mammary gland. The goal of this paper was to evaluate an ability of chosen methods to reach the SCC reliable results in vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
1
7
0
3
Order By: Relevance
“…Approximately 1 µL of milk was automatically aspirated into a small disposable cassette and stained with propidium iodide, which fluoresces when bound to DNA. The cassette was then inserted into the DCC and the SCC measured within 45 s. The DCC method has been validated for bovine milk at 4°C and 37°C against the Fossomatic (Foss, Hillerød, Denmark) and direct microscopic methods (Sarikaya and Bruckmaier, 2006;Malinowski et al, 2008;Kawai et al, 2013;Hanuš et al, 2014) and was used as the reference method in the study reported here. The DCC method has a measurement range of 10,000 to 4,000,000 cells/mL and the manufacturer reports repeatability (coefficients of variation) of 12% at 100,000 cells/mL and 8% at 400,000 cells/mL.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Approximately 1 µL of milk was automatically aspirated into a small disposable cassette and stained with propidium iodide, which fluoresces when bound to DNA. The cassette was then inserted into the DCC and the SCC measured within 45 s. The DCC method has been validated for bovine milk at 4°C and 37°C against the Fossomatic (Foss, Hillerød, Denmark) and direct microscopic methods (Sarikaya and Bruckmaier, 2006;Malinowski et al, 2008;Kawai et al, 2013;Hanuš et al, 2014) and was used as the reference method in the study reported here. The DCC method has a measurement range of 10,000 to 4,000,000 cells/mL and the manufacturer reports repeatability (coefficients of variation) of 12% at 100,000 cells/mL and 8% at 400,000 cells/mL.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The reference method for determining SCC in this study was the DeLaval cell counter (DCC; DeLaval International AB, Tumba, Sweden). The DCC method has been validated for bovine milk at 4 and 37°C against the Fossomatic (Foss, Hillerod, Denmark) and direct microscopic methods (Sarikaya and Bruckmaier, 2006;Malinowski et al, 2008;Kawai et al, 2013;Hanuš et al, 2014). The DCC is a portable automatic cell counter, with a reported measurement range of 10,000 to 4,000,000 cells/mL.…”
Section: Milk Analysis For Sccmentioning
confidence: 99%
“…The manufacturer reported a coefficient of variation of 12% at 100,000 cells/mL, 8% at 400,000 cells/mL, and 7% at 1,000,000 cells/mL. In a separate study, the reference method was linear with the Fossomatic and direct microscopic tests when analyzing bovine milk samples at 0–6°C, but read approximately 12% lower than those 2 tests . Samples were measured with the DCC at the UIDRF within 2 hours of collection at room temperature (approximately 20°C; estimated range, 15–30°C) as recommended by the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
“…In a separate study, the reference method was linear with the Fossomatic and direct microscopic tests when analyzing bovine milk samples at 0-6°C, but read approximately 12% lower than those 2 tests. 24 Samples were measured with the DCC at the UIDRF within 2 hours of collection at room temperature (approximately 20°C; estimated range, 15-30°C) as recommended by the manufacturer. Milk was drawn up using a piston into a single-use cassette that then was inserted into the DCC unit and analyzed.…”
Section: Somatic Cell Count Determinationmentioning
confidence: 99%